2015
DOI: 10.1108/bpmj-07-2014-0068
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement due to IT adoption

Abstract: Purpose – The purpose of this paper is to provide an analysis on the relationship between information technology (IT) adoption and its usage and firm performance (banking and software firm) in India. Firm performance was measured with the help of three important variables: efficiency, effectiveness and productivity. Each one of the above has been described with a set of pretested questionnaires. Banks in India, in particular are geared for comprehensive banking solutions with extensive branch n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The degree of servitization may also have an impact on IT tools' use intensity. Previous research reported that servitized firm's performance benefits from implementing IT tools (e.g., Behera, Nayak, and Das, ; Nakata, Zhu, and Kraimer, ), although service innovation research has not provided empirical evidence of this. However, the characteristics of services and service innovation may explain servitized firms' lower IT use intensity.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…The degree of servitization may also have an impact on IT tools' use intensity. Previous research reported that servitized firm's performance benefits from implementing IT tools (e.g., Behera, Nayak, and Das, ; Nakata, Zhu, and Kraimer, ), although service innovation research has not provided empirical evidence of this. However, the characteristics of services and service innovation may explain servitized firms' lower IT use intensity.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Bharadwaj (2002) states that the main difference between successful firms and less successful firms is the efficient use of information technology. Behera et al (2015) agree with Bharadwaj's (2002) statement by saying that IT adoption by a firm is very profitable for its stakeholders and this enables the growth of the organization. To strengthen Bharadwaj's (2002) and Behera et al (2015) findings, many studies have shown that IT adoption has helped to improve firm performance.…”
Section: Purpose Of the Studymentioning
confidence: 71%
“…Behera et al (2015) agree with Bharadwaj's (2002) statement by saying that IT adoption by a firm is very profitable for its stakeholders and this enables the growth of the organization. To strengthen Bharadwaj's (2002) and Behera et al (2015) findings, many studies have shown that IT adoption has helped to improve firm performance. Neirotti and Paolucci (2011)…”
Section: Purpose Of the Studymentioning
confidence: 71%
See 1 more Smart Citation
“…e functional strategy depends and must be well defined and aligned with the corporative and the business strategies. According to Sharma and Fisher [107], the main types of functional strategies are: production strategies [108], I + D strategies [109], marketing strategies [110], human resources strategies [111,112], technological strategies [113], organizational strategies [114], and financial strategies [115]. It is considered that the production strategy has been the most effective in the past and will continue to receive the maximum priority in the next years.…”
Section: Business Strategymentioning
confidence: 99%